IN THE EXPERIENCE OF THE INTERNATIONAL SYSTEM OF PROFESSIONAL EDUCATION EXISTING PROFESSIONAL COMPETITIONS - Khudayberdiyev Zayniddin Yavkachevich; Sharapov Ilkhom Bakhodir ugli (American Journals, 2024)
This article is aimed at highlighting the experience of competitions held in the world's leading professional education systems, their types, organizational methods, and their impact on young professionals.
Keywords: Professional education skills, qualifications, experience, competition, methods WorldSkills, ASEAN Skills, EuroSkills, Abilympics, SkillsUSA, China Skills.